3D printing coaxial fiber electrodes towards boosting ultralong cycle life of fibrous supercapacitors. (1st June 2021) - Lu, Hongyu; Peng, Qihe; Wang, Zhengshang; Zhao, Jingxin; Zhang, Xiaonan; Meng, Leichao; Wu, Jiang; Lu, Zhengxin; Peng, Jianhong; Li, Xifei
Abstract: Fiber-shaped asymmetric supercapacitors (FASCs) with high electrochemical performance have become an important component of modern wearable fiber-shaped electronic devices. However, terrible cycling stability restricts their further development in energy storage fields. The most common strategy is to coat the carbon layer on the surface of the electrode materials, whereas the carbon layer is prone to peel off during bending process, which decrease the cyclic stability of the electrodes or devices. To overcome this challenge, the coaxial fiber electrodes have been achieved via 3D printing direct ink writing (DIW) technology and the FASC device has the excellent electrochemical cycle performance owing to the compact architectures of the positive and negative electrode. Benefited from the suitable charge match of two electrodes and the uniformity of carbon layer coated on the surface of electrodes, the as-fabricated FASC device embraces high areal capacitance of 318.82 mF cm -2, superior areal energy density of 143.15 μWh cm -2, and excellent long-term cycling performance with capacitance retention of 98.63% after 12, 000 cycles. Graphcal abstract: The fiber-shaped asymmetric supercapacitor was constructed by twisting two 3D printing coaxial fiber electrode, which exhibits ultralong cyclic stability and wearability. Image, graphical abstract